ISU SARA (SUKU, AGAMA, RAS ANTAR GOLONGAN) DALAM PEMILU / PILKADA - fany - lestari (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2018)
ABSTRACTSARA issues are trend that being used by elections participant in competing the political opponent in the elections. Some SARA issues offently used when the political opponents are minority based on ethnic also religion. Nationalism being considered lower now because voters only see ethnics, religions, races and community or group not on capabilities and candidate integrity. We must see elections as a political activity without ethnics, religions, races and community differences. SARA issues cause unfair competition in general elections / local elections because is a negative campaign to tackle the political opponent. People that also as civil society are one part that should be involved in many efforts to change voters mindset to make the elections as a facilities to seek quality’s leader. As a country with diversity, it should be mature enough for us to use our political rights to vote using rationality not based on primordialism only. General elections / local election should be filled with unity among diversity, giving the same chance to do politic without discrimination, but when it comes to voting rights so it is personal right for everyone without coercion for anyone. Political educations are tools to educate election participants and voters to use their rights wisely and with integrity to make democratic elections.Keywords : SARA, Politic campaign, Nationalism, Fair competition